1989
DOI: 10.1002/jcp.1041380305
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between heparan sulfate metabolism and hepatoma growth

Abstract: A rat hepatoma cell line (Gershenson et al., Science, 170:859-861, 1970) contains a dynamic steady-state pool of free heparan sulfate (HS) chains in the nucleus that increases in amount when growing cells reach confluence (Fedarko and Conrad, J. Cell Biol., 102:587-599, 1986). In logarithmically growing cells labeled with 35SO4(2-) steady-state levels of [35SO4]HS in the nucleus are altered by a variety of culture conditions. Rapidly dividing cells (doubling time = 18-22 h) growing under optimized conditions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 49 publications
2
34
1
1
Order By: Relevance
“…It is of note that cell-surface HSPG accumulates in the nucleus and regulates the growth of a hepatoma cell line [29]. Further study will elucidate the HGF-signal transduction mediated by each pathway.…”
Section: Discussionmentioning
confidence: 98%
“…It is of note that cell-surface HSPG accumulates in the nucleus and regulates the growth of a hepatoma cell line [29]. Further study will elucidate the HGF-signal transduction mediated by each pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups have reported the presence of HS chains in the nucleus of various cell types [5][6][7][39][40][41] and demonstrated that HSPGs may regulate the internalization and nuclear uptake of FGF-1 and FGF-2. [7][8][9] It was also suggested that a correlation exists between nuclear localization of HS and the growth rate of hepatoma cells, and that both glypican and biglycan participate in the regulation of C6 glioma cell proliferation and survival through a direct involvement of HSPGs in nuclear processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although these glycosaminoglycans are usually associated with extracellular matrices, they are also present at the cell surface (20) and within the cytoplasm and nucleus of several cell types (21)(22)(23). Although their intracellular functions are not yet established, it is noteworthy that a specific subpopulation of heparan sulfate is targeted to the nucleus of hepatoma cells (21,24) and that heparin inhibits Fos-and Jun-induced transcription events in vitro and in situ within the nucleus (25). The latter events may occur via competition with DNA binding (18,25).…”
mentioning
confidence: 99%